Preparation of teachers at Makerere University for the teaching of g eography in selected secondary schools in Kampala district - Naluyima, Judith O. (Kampala, 2012)
Unpublished thesis (M.Ed. CTMS) - Makerere University, 2012
Includes bibliographical references.
Keywords: Teachers -- Trainig of -- Makerere University -- Uganda. -- Makerere University -- Uganda; Geography -- Study and teaching -- Uganda. -- Uganda. -- Makerere University -- Uganda